Seismic Refraction Analysis for Subsurface Layer Identification: A Case Study at the Kalimantan Institute of Technology - Juniar, Firza; Rahmania, Rahmania; Arisalwadi, Meidi; Nur, Adrian Rahmat; Sastrawan, Febrian Dedi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Institut Teknologi Kalimantan (ITK) is one of the state universities that is currently actively developing educational facilities and infrastructure. Geologically, ITK is built on the Kampung Baru sedimentary rock formation, which has a low level of soil bearing capacity. This can cause damage to the building if the determination of the foundation depth does not have the right bearing data. The study aimed to determine the subsurface structure in the ITK campus area based on the speed of seismic wave propagation and to determine the distribution of subsurface hard rock layers in the ITK campus development area. The research methods used are field surveys, data acquisition, seismic wave recording data, travel time curves, 2D fast wave propagation models, and interpretation. The research results obtained the value of the first layer wave propagation velocity on tracks 1,2,3,4, and 5, ranging from 128.7 - 201.9 m/s. The second layer on tracks 1,2,3,4, and 5 ranged from 272.4 - 428.0 m/s. The research concludes that it can determine the subsurface structure based on the fast wave propagation value, geological conditions, and outcrop findings, namely the first layer in the form of soil and the second layer in the form of sand clay. Development can be carried out in the passive clay layer by laying the foundation